The reconstructive strategy for pelvic oncological surgery with various types of MS-VRAM flaps. Issue 7 (July 2022) - Chen, Qiao; Dong, Ruijia; Zeng, Ang; Teng, Yue; Liu, Zhifei; Zhu, Lin; Long, Fei; Si, Loubin; Yu, Nanze; Wang, Xiaojun
Summary: Background: Muscle-sparing vertical rectus abdominis myocutaneous (MS-VRAM) flaps are widely used in pelvic reconstruction. Aiming at optimal reconstructive outcomes, flap design and modification should be individualized to restore various kinds of defects. Objective: Summarize an empirical strategy about MS-VRAM selection for different pelvic and perineal reconstructions. Methods: Thirty patients who underwent total pelvic exenteration and pelvic reconstruction surgery from 2009 to 2017 were enrolled. The patients were divided into four groups according to the type of MS-VRAM-based flap used in the procedure: the modified long vertical flap ( n  = 10), the wrapping flap ( n  = 6), the de-epithelialized flap ( n  = 6), and the cork flap ( n  = 8). The follow-up period was 1 year after the surgery. Flap size, drainage volume, postoperative satisfaction, and complications were recorded, and postoperative photographs were collected. Results: All of the patients achieved satisfying effect under the targeted reconstruction strategy. Of the four groups, the accurate cork flap finally acquires higher satisfaction, the shortest hospital stay, and the least total drainage volume. Meanwhile, the incidence of complications was not increased compared with the other groups. Conclusions: A new reconstructive strategy for pelvic reconstruction was established. Functional or non-functional reconstruction was accomplished by using various MS-VRAM flaps. Among them, the cork flap is the most economical flap to reconstruct pelvic floor defects with minimal tissue requirement and donor trauma.